(3GdCQHYhf MOjKGs - (3GdYGedj, GdMGQKj, GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3GdfHj Udi Gddg Ydjg hBdg Hbhdg(B: (3dG jabg GdYHO cd Gdabg MJi jebJ GdfGS aj PGJ Gddg hMJi jQi ddbQBf hLhgG cKjQI(B... (3GdMOjK GdKGfjs
(3BNQgG (B:s
(3hScGfg Ydi WHbGJ ef eJaGhJI aj GddWGaI hGdcKGaI hbHM GdUhQI hMSfgG (B... (3LejY GdMhGS GdXGgQI hGdHGWfI (B... (3hGdGdGe GdfaSjI hGdLSeGfjI hbO fSH GdYdGeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B102s
(3GdPQjYI HQbe(B: 2146s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs